2020
DOI: 10.1016/j.celrep.2020.108184
|View full text |Cite
|
Sign up to set email alerts
|

SFPQ Depletion Is Synthetically Lethal with BRAFV600E in Colorectal Cancer Cells

Abstract: Highlights d Loss of SFPQ/PSF causes apoptosis in BRAF V600E -driven cancer cells d BRAF-mutant cells depend on SFPQ to maintain faithful DNA replication d SFPQ depletion upon BRAF V600E induction causes R-loop formation d Inhibition of ATR kinase Chk1 sensitizes BRAF V600E cells to replication stress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…Our study also identified further cancer traits in CRC cell clusters with relevance to therapy. For instance, TC1 cells were defined by high levels of replication stress, which can be functionally associated with high MAPK activity (Sheu et al , 2012; Klotz-Noack et al , 2020). Tumors with high TC1 cell content were strongly positive for PARP, an important therapeutic target (Sun et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also identified further cancer traits in CRC cell clusters with relevance to therapy. For instance, TC1 cells were defined by high levels of replication stress, which can be functionally associated with high MAPK activity (Sheu et al , 2012; Klotz-Noack et al , 2020). Tumors with high TC1 cell content were strongly positive for PARP, an important therapeutic target (Sun et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is a multifunctional RBP and regulates a wide range of cellular processes, including pre-mRNA splicing, transcription, nuclear RNA retention, paraspeckle formation, RNA transport, DNA repair, translation, apoptosis, and response to viral infection 17 23 . Though the functional impact of SFPQ has been shown in various diseases such as neurological 24 26 , immune-metabolic 27 , genetic 28 , and cancer 29 , 30 , there is no prior report of changes in the SFPQ expression level in CF diseased state. Here, we find reduced levels of nuclear-localized SFPQ protein in F508del-CFTR CF lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It binds to both DNA and RNA and is implicated in the regulation of gene expression pathways, including alternative splicing, transcription, nuclear RNA retention, paraspeckle formation, RNA transport, DNA repair, translation, apoptosis, and response to viral infection 17 23 . The involvement of SFPQ has been demonstrated in several diseases such as neurological 24 26 , immune-metabolic 27 , genetic 28 , and cancer 29 , 30 . However, whether SFPQ has any role in the regulation of CF lung disease is completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is a multifunctional RBP and regulates a wide range of cellular processes, including pre-mRNA splicing, transcription, nuclear RNA retention, paraspeckle formation, RNA transport, DNA repair, translation, apoptosis, and response to viral infection [17][18][19][20][21][22][23] . Though the functional impact of SFPQ has been shown in various diseases such as neurological [24][25][26] , immune-metabolic 27 , genetic 28 , and cancer 29,30 , there is no prior report of changes in the SFPQ expression level in CF diseased state. Here, we find reduced levels of nuclearlocalized SFPQ protein in F508del-CFTR CF lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%